2020
DOI: 10.1038/s41598-020-72563-w
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of tree shrew to SARS-CoV-2 infection

Abstract: Since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) became a pandemic event in the world, it has not only caused huge economic losses, but also a serious threat to global public health. Many scientific questions about SARS-CoV-2 and Coronavirus disease (COVID-19) were raised and urgently need to be answered, including the susceptibility of animals to SARS-CoV-2 infection. Here we tested whether tree shrew, an emerging experimental animal domesticated from wild animal, is susceptible to SARS-CoV-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 47 publications
5
80
0
2
Order By: Relevance
“…Recently, SARS-CoV-2 infection has been reported in cats, dogs, minks, tigers, and lions (28,31,(35)(36)(37). Furthermore, experimental studies documented the susceptibility of different animal species to SARS-CoV-2, such as mice, hamsters, cats, ferrets, non-human primates, and treeshrews (6,24,30,38,39). The natural and experimental infection to animals is shown in Figure 1.…”
Section: Possible Animal Reservoirsmentioning
confidence: 99%
“…Recently, SARS-CoV-2 infection has been reported in cats, dogs, minks, tigers, and lions (28,31,(35)(36)(37). Furthermore, experimental studies documented the susceptibility of different animal species to SARS-CoV-2, such as mice, hamsters, cats, ferrets, non-human primates, and treeshrews (6,24,30,38,39). The natural and experimental infection to animals is shown in Figure 1.…”
Section: Possible Animal Reservoirsmentioning
confidence: 99%
“…During replication, the viral spike (S) envelope glycoprotein and the nucleoprotein (NP) are highly transcribed [ 7 ]. Through experimental infection studies, SARS-CoV-2 has been shown to infect non-human primates, cats, ferrets, bats, hamsters and tree shrews but does not productively infect pigs, dogs or poultry [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Sporadic infections of domestic cats and dogs, as well as large captive felids and farmed mink [ 20 , 21 , 22 , 23 , 24 ] have been reported and are thought to be reverse-zoonoses.…”
Section: Introductionmentioning
confidence: 99%
“…Based on ACE2 similarities, a range of different animals have been used as models. Experimental infections in dogs (10), cats (10-13), ferrets (10,14), hamsters (15,16), rhesus macaques (17), tree shrew (18), cynomolgus macaques (19), African green monkey (20), common marmosets (21), rabbits (22), and fruit bats (23) have shown that these species are susceptible to SARS-CoV-2, and experimentally infected cats, tree shrews, hamsters and ferrets could also transmit the virus. In contrast, experimental infection of pigs and several poultry species with SARS-CoV-2 proved to be unsuccessful (10,23,24).…”
mentioning
confidence: 99%